Saturday Diary: Far from Nepal, Pittsburgh Felt Like Home - Adhikari, Deepak (Journal of International Students, 2011)
When I arrived in Pittsburgh in the end of March, I got a new address: 10 Allegheny Center, Apt. 115. Here, on the North Side of this bustling city, I sought to create a home away from home. A framed picture of Pittsburgh at night adorned the most expansive white wall, but I wanted to make my Allegheny Center apartment Nepali, too. I hung posters from Nepal–of Kumari, a living goddess; of Swayambhu, a Buddhist temple in Kathmandu; of Nyatapola, a temple in the ancient city of Bhaktapur. I uploaded Nepali songs to my laptop and hummed them as I cooked Nepali food.